2012
DOI: 10.1155/2012/217037
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species, Oxidative Damage, and Antioxidative Defense Mechanism in Plants under Stressful Conditions

Abstract: Reactive oxygen species (ROS) are produced as a normal product of plant cellular metabolism. Various environmental stresses lead to excessive production of ROS causing progressive oxidative damage and ultimately cell death. Despite their destructive activity, they are well-described second messengers in a variety of cellular processes, including conferment of tolerance to various environmental stresses. Whether ROS would serve as signaling molecules or could cause oxidative damage to the tissues depends on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

83
2,908
6
101

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 3,881 publications
(3,098 citation statements)
references
References 254 publications
(364 reference statements)
83
2,908
6
101
Order By: Relevance
“…It is believed that the protection of plants against the accumulation of H 2 O 2 results from the joint action of the CATs and the APXs. The affinity of different APXs and CATs for H 2 O 2 suggests that APX is responsible for the fine modulation signal of the reactive species, while catalase removes excess H 2 O 2 during stress (Gill and Tuteja, 2010;Sharma et al, 2012. Increases of SOD activity were observed in various proportions among the soybean plants coexisting with ryegrass compared to the control plants (Table 3). When the effect of the ratio was analyzed, it was found that for the soybean coexisting with the susceptible biotype, the ratio of 75:25 resulted in lower enzyme activity than the other SOD; however, when coexisting with the resistant ryegrass, there was no significant difference.…”
Section: Resultsmentioning
confidence: 99%
“…It is believed that the protection of plants against the accumulation of H 2 O 2 results from the joint action of the CATs and the APXs. The affinity of different APXs and CATs for H 2 O 2 suggests that APX is responsible for the fine modulation signal of the reactive species, while catalase removes excess H 2 O 2 during stress (Gill and Tuteja, 2010;Sharma et al, 2012. Increases of SOD activity were observed in various proportions among the soybean plants coexisting with ryegrass compared to the control plants (Table 3). When the effect of the ratio was analyzed, it was found that for the soybean coexisting with the susceptible biotype, the ratio of 75:25 resulted in lower enzyme activity than the other SOD; however, when coexisting with the resistant ryegrass, there was no significant difference.…”
Section: Resultsmentioning
confidence: 99%
“…CATs have a very fast turnover rate, but a much lower affinity for H 2 O 2 than APX. They are known to remove H 2 O 2 produced in the peroxisomes by photorespiration (Noctor et al 2000), β-oxidation of fatty acids and other enzyme systems such as xanthine oxidase (XOD) coupled to SOD (Sharma et al 2012). CAT activity has also been found to decrease under conditions that suppress photorespiration, such as elevated CO 2 (Azevedo et al 1998) and high light intensities (Shang and Feierabend 1999).…”
Section: Resultsmentioning
confidence: 99%
“…Catalase is an important enzyme that catalyzes the decomposition of hydrogen peroxide to water and oxygen. This enzyme protects the cells of organisms from oxidative damage by ROS (Sharma et al 2012). The depletion of this enzyme activity in organisms may cause toxic effects due to the accumulation of hydrogen peroxide in animal cells (Ferraris et al 1996).…”
Section: Discussionmentioning
confidence: 99%